Wolbachia infection reduces blood-feeding success in the dengue fever mosquito, Aedes aegypti. - Andrew P Turley; Luciano A Moreira; Scott L O'Neill; Elizabeth A McGraw (Public Library of Science (PLoS), 2009)
BACKGROUND: The mosquito Aedes aegypti was recently transinfected with a life-shortening strain of the endosymbiont Wolbachia pipientis (wMelPop) as the first step in developing a biocontrol strategy for dengue virus transmission. In addition to life-shortening, the wMelPop-infected mosquitoes also exhibit increased daytime activity and metabolic rates. Here we sought to quantify the blood-feeding behaviour of Wolbachia-infected females as an indicator of any virulence or energetic drain associated with Wolbachia infection. METHODOLOGY/PRINCIPAL FINDINGS: In a series of blood-feeding trials in response to humans, we have shown that Wolbachia-infected mosquitoes do not differ in their response time to humans, but that as they age they obtain fewer and smaller blood meals than Wolbachia-uninfected controls. Lastly, we observed a behavioural characteristic in the Wolbachia infected mosquitoes best described as a "bendy" proboscis that may explain the decreased biting success. CONCLUSIONS/SIGNIFICANCE: Taken together the evidence suggests that wMelPop infection may be causing tissue damage in a manner that intensifies with mosquito age and that leads to reduced blood-feeding success. These behavioural changes require further investigation with respect to a possible physiological mechanism and their role in vectorial capacity of the insect. The selective decrease of feeding success in older mosquitoes may act synergistically with other Wolbachia-associated traits including life-shortening and viral protection in biocontrol strategies.